How the pandemic shaped presenteeism trends between healthcare and non-healthcare workers using the Korean working conditions surveys (2010–2023) - Ari Min; Yoonjung Ji; Wonhee Baek (Scientific Reports)
Abstract Presenteeism, the act of working while unwell, presents serious risks to both workers and organizations, especially in healthcare, where it directly affects patient-care quality. The COVID-19 pandemic has intensified these risks, particularly for healthcare workers facing increased workload pressure. Although the impact of presenteeism on workers has been widely studied, a critical gap remains in our understanding of how its patterns have shifted over time. Therefore, this study examined presenteeism trends using the Korean Working Conditions Surveys (2010–2023), focusing on healthcare workers and the effects of age and sex before and after the COVID-19 pandemic. The results indicated that presenteeism peaked in 2014, declined sharply in 2020, and reached its lowest level by 2023. Healthcare workers exhibited high presenteeism rates prior to the pandemic; however, during and after the pandemic, these rates decreased rapidly and ultimately became lower than those of non-healthcare workers. Older and female healthcare workers showed higher presenteeism (i.e., were more likely to work while ill), and these trends persisted even after the pandemic. These findings underscore the need for sex- and age-sensitive workplace interventions for healthcare workers to promote healthier work environments and mitigate the risk of presenteeism.